Prevention of Offenses in the Field of Environmental Protection in the Republic of Karakalpakstan - Jenesbaevna, Gulbakhar Yazhenesbaevna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article reveals the essence and significance of the prevention of offenses in the field of environmental protection in the Republic of Karakalpakstan, provides directions for the development of prevention of offenses in the field of environmental protection.